The Journey of Self-Actualization of the Main Character in the Film Bolehkah Sekali Saja Kumenangis: A Humanistic Psychology Perspective by Abraham Maslow - Wahyuningtyas, Cindy; Sodiq, Syamsul (Jurnal Pembelajaran Bahasa dan Sastra, 2025)
This study aims to examine the process of the main character’s self-actualization journey in the film Bolehkah Sekali Saja Kumenangis based on Abraham Maslow’s humanistic psychology theory. The research problem is focused on how the main character’s self-actualization journey in achieving self-actualization based on Maslow’s hierarchy of needs, as well as the psychological impacts caused by fulfilling these needs. The method used is qualitative with a literary psychology approach. The data source is the entire film Bolehkah Sekali Saja Kumenangis with research data in the form of dialogue, plot, setting, intonation, visuals of the main character, expressions, body movements, audio/music. The data collection techniques used are documentation and note-taking techniques. The data analysis technique used is the Miles & Huberman model. The results of this study indicate that there are 12 processes of fulfilling the main character’s needs to achieve self-actualization, which are influenced by various factors, such as internal factors, external factors, or both combined. The psychological impacts also vary, some are negative and positive. Negative impacts include anxiety, confusion, psychological exhaustion, emotional loneliness, low self-esteem, and despair. Positive impacts include health and calm, feeling safe, feeling loved, feeling accepted in the social environment, self-confidence, daring to refuse, self-acceptance, appreciation, independence, and forgiveness. In conclusion, the process of self-actualization of the main character is not easy and is full of challenges. Failure to fulfill the needs often occurs at the second level, namely the need for safety and security, due to the influence of external factors, in the form of the father’s dominance. This results in negative impacts that often arise at this stage. Then, positive impacts appear more in the fifth stage, when the main character has achieved self-actualization.